2010
DOI: 10.1063/1.3354105
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the electrical transport properties in a Ni2MnGa single crystal: Experiment and theory

Abstract: Electrical transport properties in ferromagnetic shape memory Ni-Mn-Ga single crystal have been investigated both in experiment and theory by analyzing electrical resistivity along different crystallographic directions during heating. The experimental results show a clear first-order martensitic transformation and a large anisotropic resistivity ͑AR͒ of 23.7% at the tetragonal martensitic phase. The theoretical conductivity ͑ =1/ ͒, estimated using first-principles calculations combined with classical Boltzman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In addition to the band splitting due to the twinned microstructure, the comparison of the ECC of austenite and martensite in Figure 1 shows a surprising fact: that the martensitic phase exhibits weak or no electron emission in its central part, i.e., there is no photoelectron signal around the Γ point, in contrast to the austenitic cubic phase. Moreover, theoretical 3D calculations of martensite also predict the photoelectron emission close to the Γ point [17,18].…”
Section: Methodsmentioning
confidence: 86%
“…In addition to the band splitting due to the twinned microstructure, the comparison of the ECC of austenite and martensite in Figure 1 shows a surprising fact: that the martensitic phase exhibits weak or no electron emission in its central part, i.e., there is no photoelectron signal around the Γ point, in contrast to the austenitic cubic phase. Moreover, theoretical 3D calculations of martensite also predict the photoelectron emission close to the Γ point [17,18].…”
Section: Methodsmentioning
confidence: 86%
“…As a consequence, hysteresis-free resistance-magnetostrain relations are obtained. This indicates that the anisotropy of the electrical resistivity along the different crystallographic directions can be neglected [60,61]. Another experiment demonstrated that the inductance of a pick-up coil at the MSMA actuator may also be used for position sensing with good accuracy [62].…”
Section: Msm Linear Actuatorsmentioning
confidence: 97%